Role of phosphorus and molybdenum on root growth, nodulation and nutrient uptake of soybean [Glycine max (L.) Merr.]: ROLE OF PHOSPHORUS AND MOLYBDENUM ON GROWTH, NODULATION AND N UPTAKE OF SOYBEAN - T SPANDANA; K BHANU REKHA; S N SUDHAKARA BABU (Journal of Oilseeds Research, 2021)
A field investigation was carried out during kharif 2015 to study the response of soybean to phosphorus and molybdenum nutrition. Results revealed that the interaction effect of phosphorus application (60 kg P2O5/ha) and molybdenumseed treatment @ 6 g/kg seed recorded significantly higher vigourindex-I (2305), vigour index- II (90), root length (21.26 cm), root volume (12.70 cm3), effective nodules/plant (37), nodule dry weight (50.73 mg), oil content (19.43 %) and molybdenum uptake by seed (4.10 g/ha). The leghaemoglobin content was highest (249 mg/g fresh weight) with P application @ 60 kg/ha and it was unaffected due to Mo seed treatment and interaction of P and Mo. Among the P levels, protein content and seed yield were significantly higher (41 % and 1784 kg/ha) with 60 kg/ha and with Mo seed treatment @ 6 g/kg seed (40.2 % and 1572 kg/ha).